Pendampingan Pembangunan Jaringan Irigasi Air Tanah untuk Mendukung Ketahanan Pangan di Desa Jatimulyo Kecamatan Plumpang Kabupaten Tuban - Prambudi, Wahyu Tri; Rowibowo, Nolo; Ariyanti, Menik; Cahyaningrum, Fibia Sentauri (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This Community Service activity aims to optimize the groundwater irrigation network to support food security in Jatimulyo Village, Plumpang District, Tuban Regency. The main problem faced by the local community is the limited surface irrigation network, especially during the dry season. The methods used in this activity include counseling, diffusion of science and technology, training, and direct mentoring to farmer groups. The results of the activity show that farmers have increased their knowledge and skills in utilizing the groundwater irrigation system efficiently. In addition, an irrigation control tank unit has been built as a pilot model. This activity proves that a participatory approach and appropriate technology can encourage farmer empowerment and provide applicable alternative solutions to increase agricultural productivity in areas facing an irrigation water crisis. This activity was carried out in collaboration with the Bengawan Solo River Basin Authority as a form of synergy between academics and stakeholders in water resource management.